Fiscal rules and unemployment - Britta Gehrke (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2017)
This paper shows how fiscal policy affects unemployment in a New Keynesian model with search and matching frictions and distortionary taxation. The model is estimated using US data that includes labor market flows and distinct fiscal instruments. Several findings stand out. First, unemployment mult ipliers for spending and consumption tax cuts are substantial, even though output multipliers turn out to be less than one. Second, multipliers for labor tax cuts ar e small. Third, fiscal rules enhance the positive effects of discretionary fiscal policy. However, these expansionary effects on the multipliers are modest compare d to earlier studies.
Keywords: E62; J20; C11; 330; Fiscal policy; Fiscal rules; Unemployment; Search and matching